Contemporary two-storey churches – acoustic investigations - Sygulska, Anna (Journal of Architecture and Urbanism, 2015)
The paper discusses the idea of two-storey churches, with insight into socio-political conditions which influenced their construction. The analysis of the issue was carried out on the basis of investigations in five two-storey churches in Poznań. The churches under investigation were: Visitation of Blessed Virgin Mary Church, Christ the King Church, Our Lady of Częstochowa Church, St. Lawrence Church, and Christ the Redeemer Church. In total, ten interiors were examined. The churches were erected in the late 70s and early 80s of the 20th century. The acoustic conditions were analyzed in terms of cubature, the shape of the interior and finishes. The upper and lower churches were compared within one building; the investigation also involved comparing the churches against each other. Moreover, functionality of the buildings was analyzed, which included aspects of acoustic as well as architectural functionality.